ADMISSION FRAILTY SCORE AS A GOOD CLINICAL SUBSTITUTE OF SOFA SCORE TO PROGNOSTICATE POST-PERCUTANEOUS CORONARY INTERVENTION PATIENTS ON ADVANCED LIFE-SUPPORT - Baig, Mirza Yousuf; Ansari, Muhammad Imran; Hassan, Mujtaba; Arif, Muhammad Shoaib; Memon, Aziz ur Rehman; Umair, Madiha; Abubaker, Jawed (Journal of Ayub Medical College Abbottabad, 2024)
Background: This study aimed to assess and compare the prognostic value of frailty score (FS), Sequential Organ Failure Assessment (SOFA) score, and additive of FS and SOFA score, at the time of admission to the coronary care unit (CCU), for the prediction of short-term poor prognosis in post-myocardial infarction (MI) patients, requiring advanced life-support. Methods: A cohort of post-MI patients admitted to CCU. The FS and SOFA score were obtained at the time of CCU admission. The prognostic value of FS, SOFA score, and FS+SOFA score was assessed to predict in-hospital and short-term follow-up mortality. Results: The study sample consisted of 312 patients: females were 27.2% (85), and the mean age was 60.32±11.51 years. A concordance rate of 51.8% was observed between admission FS (‰¥3) and SOFA score (‰¥9). A total of 67.3% (210) patients were categorized as moderate to severely frail (‰¥3), while the SOFA score identified 26.0% (81) high-risk (‰¥9) patients. The receiver operating characteristics (ROC) analysis showed an area under the curve (AUC) of 0.707 [0.638-0.776], 0.764 [0.704-0.825], and 0.783 [0.724-0.842] for in-hospital mortality and 0.684 [0.621-0.746], 0.718 [0.659-0.778], and 0.744 [0.687-0.801] for 180-day cumulative mortality against FS, SOFA, and FS+SOFA score, respectively. A hazard ratio of 2.75 [1.61-4.71] and 2.51 [1.68-3.75] were observed for mortality during 180-day follow-up among patients with FS ‰¥3 and SOFA score ‰¥9, respectively. Conclusion: CCU admission Frailty Score is a good clinical substitute for SOFA score for an early prognostication of post-MI patients on advanced life-support.